Improving Students' Critical Thinking Skills by Developing and Implementing Case-Based Learning - Safitri, Sani; Alwi, Zahra; Suwitri, Endang; Alfiandra, Alfiandra; Arviansyah, Muhammad Reza; Imawati, Sri (Journal of Innovation in Educational and Cultural Research, 2026)
One of the most crucial competencies for educators is the ability to create meaningful and effective learning experiences. This research aims to develop and implement learning tools—specifically lesson plans and textbooks—using the Case approach for a Student Development course. The study employs Rowntree’s development model, consisting of three main stages: planning, development, and iterative evaluation with revisions based on expert input and trial results. The lesson plans developed in this study achieved a strong average validity score of 4.57, indicating a high level of alignment with learning objectives and curriculum standards. The textbooks that support the lesson plan were also validated, scoring 3.98 in terms of design and 4.203 for content quality, both considered valid to very valid. Practicality testing involved both individual and group trials, demonstrating that the materials are user-friendly, applicable, and effective in classroom settings. To assess effectiveness, students’ critical thinking skills were measured before and after the implementation. Results showed a significant increase, with pre-test scores averaging 61.6 and post-test scores reaching 91.8, yielding an N-gain of 0.786, which is classified as high. These findings demonstrate that Case-based learning tools can foster student engagement, contextual understanding, and higher-order thinking skills, making them highly effective for educational use in similar contexts.